Learning Strategies Employed by Non-English Department Students during Native Speaker Interview Sessions - Survia, Desty; Idris, Meity Hadzriana (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2026)
The study participants were 46 first-semester students of the Early Childhood Islamic Education (PIAUD), Islamic Elementary School Education (PGMI), and Islamic Religious Education (PAI) study programs at STIT INSIDA Jakarta who were taking general English courses in the first semester of 2024. Data were collected through semi-structured interviews following interviews with native English speakers. The data were analyzed using thematic analysis based on the Oxford classification of language learning strategies, including memory, cognitive, compensatory, metacognitive, affective, and social strategies. The results showed that students faced several major obstacles, namely limited vocabulary, pronunciation difficulties, and low confidence when speaking. To overcome these obstacles, students most often used compensatory strategies, such as paraphrasing, using simple sentences, and body movements. In addition, cognitive and metacognitive strategies were also widely used in the form of question practice, answer planning, monitoring, and evaluating speaking performance. Affective strategies helped students manage anxiety, while social strategies supported learning through interactions with peers and native speakers. These findings suggest that interview sessions with native speakers encourage the use of a variety of language learning strategies that contribute to the improvement of vocabulary and speaking confidence of non- English Department students. Keywords: Language Learning Strategies Non-English Department Students, Interview , Native Speaker, Speaking Skill